Environmental Abatement and Intergenerational Redistribution - A. Lans Bovenberg; Ben J. Heijdra (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
This paper employs an overlapping-generations model to explore the impact of public abatement on private investment and the intergenerational distribution of welfare. Whereas public abatement benefits the oldest generations in terms of non-environmental welfare, future generations gain most in terms of environmental welfare. The overall benefits tend to be smallest for the generations born at the time of the unanticipated policy shock. Public debt policy, however, can be employed to ensure that welfare gains are distributed more equally across the various generations. Such a policy implies that natural capital crowds out man-made capital.
Keywords: 330